Rejuvenating Organic Soil Behavior with Crushed Waste Concrete: Experimental and Mineralogical Investigations - Ayah Almsedeen; Ishak, Mohd Fakhrurrazi; Nurmunira Muhammad; Sumi Siddiqua; Muhammad Nizam Zakaria (International Journal of Integrated Engineering, 2024)
Urban regions are currently grappling with the mounting challenge of managing significant volumes of solid waste, especially from building and demolition materials. This study explores the utilization of crushed waste concrete (CWC), a substantial component of solid waste, for organic soil stabilization. Various percentages (10%, 15%, and 20%) of crushed waste concrete were added to organic soil. Subsequently, a comprehensive series of laboratory tests were conducted, including compaction tests using the standard proctor test, unconfined compressive strength (UCS) tests, and Physicochemical assessments comprising of pH, SEM-EDX, and XRD analyses. The results of the experimental tests revealed interesting trends. As the crushed waste concrete percentages increased, there were corresponding increases and decreases in the organic soil’s maximum dry density and optimum water content, respectively. Notably, the UCS values of the organic soil exhibited an approximate 594% enhancement when the CWC percentage was about 10%. The SEM-EDX and XRD analyses provided valuable insights, indicating an improvement in the soil structure and the presence of new cementitious materials such as calcium-aluminate-hydrate (CAH) and calcium-silicate-hydrate (CSH) resulting from the interaction between crushed waste concrete and organic soil. This study demonstrates the potential of crushed waste concrete as an effective agent for organic soil stabilization, offering a sustainable approach for repurposing solid waste and mitigating soil-related challenges in urban regions. The findings suggest promising prospects for further exploration and application of this eco-friendly technique in civil engineering and construction practices, contributing to waste reduction and environmental preservation.